Analisis Bibliometrik dan Perkembangan Penelitian Perbedaan Gender dalam Komunikasi - Samiri, Muliani; Kasman, Nuraeni; Nonci, Nurjannah; Jumriani (Jurnal Komunikasi Profesional, 2024)
Research on gender differences in communication can help understand how gender stereotypes affect the way people communicate This study aims to determine the development of research with the theme "Gender Differences In Communication" from 1988 to 2022. The research method used is qualitative research using literature review. Data collection was carried out by accessing journals on Scopus and obtaining 40 articles with high citations between 1988 and 2022. The data collected was analyzed using the Vosviewer and Nvivo 12 Plus applications. The results showed that there were 40 journals that discussed "Gender Differences In Communication" with the United States being the largest contributor of articles. The limitation of this research is that the articles reviewed are only obtained from the Scopus database, so they do not have comparable data. Consequently, further research needs to use a comparative analytic approach involving the Scopus database and the Web of Sciences